Effects of soil macro- and mesofauna on litter decomposition and soil organic matter stabilization - Frouz, Jan (Geoderma, 2018)
Soil fauna consumes substantial amounts of litter and can even consume the entire annual litterfall in some ecosystems. The assimilation efficiency of fauna may reach 50% but is usually much smaller. Soil fauna may affect soil organic matter (SOM) dynamics not only by assimilating litter but also by modifying the soil environment at many spatiotemporal scales. Litter processing by fauna usually results in a short-term increase in microbial activity in feces; this activity than decreases such that feces over the long term may decompose more slowly than the original litter. During passage through the guts of litter-feeding fauna, litter modifications include fragmentation, consumption of associated microorganisms, pH and redox changes, removal of easily decomposed polysaccharides, increase in the proportion of lignin, and decrease in soluble polyphenols and carbon:nitrogen (C:N) ratios. The coating of litter with clay during passage through earthworms reduces microbial access to the litter as well as conditions for microbial activity by reducing the diffusion of nutrients and oxygen. At a larger scale, soil fauna affects leaching and the release of particulate organic matter (POM), which in turn affect microbial activity in soil. Fauna also affects the distribution of organic matter in the soil profile and determine whether litter decomposes on the soil surface or as POM bound to soil particles, which substantially affects the microbial community and the rate of decomposition. Fauna affects the amount of organic matter entering different SOM pools, and this effect depends on litter quality and the degree of soil C saturation. At an even larger scale, fauna can change the soil profile, soil properties, and the plant community, which may in turn affect microbial activity and the decomposition rate. The effect of soil fauna on litter decomposition and soil C storage can be positive or negative. Faunal effects tend to be greatest in ecosystems under transition, e.g. ecosystem developing after some disturbance during primary or secondary succession. •Soil fauna consume substantial amounts of litter•Fauna affect the amount of organic matter entering different SOM pools•The effect of soil fauna on litter decomposition and soil C storage can be positive or negative.•Faunal effects tend to be greatest in ecosystems under transition.